The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1109/tdei.2020.009115
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Breakdown Study in CO2 and CO2-O2 Mixtures in AC, DC and Pulsed Electric Fields at 0.1–1 MPa Pressure

Abstract: In this paper, the results of AC, DC and 2/160 µS impulse electrical breakdown experiments of CO 2 and CO 2-O 2 mixtures in weak and strongly non-uniform fields are presented. In weakly non-uniform fields, the electrical breakdown field approximately follows 11 when stressed with both AC and DC (positive and negative) waveforms. For positive impulse, the breakdown voltage is higher and the time lag to breakdown is scattered, indicating a lack of starting electrons from CO 2 gas. The breakdown strengths of CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…When such a thermalized plasma channel is formed, the current rises sharply and the voltage across the gap collapses. It was found that in the present experimental conditions, the thermalisation time (i.e., the time interval between the first significant current spike and the moment of the sharp rise in current) is almost the same, ~ (11)(12) ns, for all tested gases and gas pressures, which indicates that this time is governed by the parameters of the pulsed power circuit used in these tests. Therefore, U br-ch is the voltage at which the initial breakdown plasma channel is formed in the gas-filled gap; the main streamer starts to develop through this channel, leading to its thermalisation.…”
Section: Pulse Generator and Diagnostic Devicesmentioning
confidence: 57%
See 4 more Smart Citations
“…When such a thermalized plasma channel is formed, the current rises sharply and the voltage across the gap collapses. It was found that in the present experimental conditions, the thermalisation time (i.e., the time interval between the first significant current spike and the moment of the sharp rise in current) is almost the same, ~ (11)(12) ns, for all tested gases and gas pressures, which indicates that this time is governed by the parameters of the pulsed power circuit used in these tests. Therefore, U br-ch is the voltage at which the initial breakdown plasma channel is formed in the gas-filled gap; the main streamer starts to develop through this channel, leading to its thermalisation.…”
Section: Pulse Generator and Diagnostic Devicesmentioning
confidence: 57%
“…The numerical values of the fitting parameters, C and D, obtained in OriginPro graphing software for each gas are given in Table 2. 11 shows Nt as a function of E/N for air, N2 and CO2 and includes: the results obtained in the present work (Ntbr as a function of Etip/N), the kinetic model results (Ntf as a function of E/N), and the results previously published in the literature, [10,11,[22][23][24], and [34][35][36][37]. Each experimental point shown in Figure 11 represents the average value obtained using 20 individual data points, the error bars show the 95% confidence interval values, (some original experimental points do not appear to have error bars as a result of these bars being too small to display relative to the size of the point).…”
Section: Breakdown Voltage and Time To Breakdown In Investigated Gasesmentioning
confidence: 77%
See 3 more Smart Citations